Implementasi Pembelajaran E-learning Matematika Siswa Kelas IV MI Al-Azhar Menganti Gresik - Nur Jannah Wanda Hamidah; Februesty Maya Lestari; Awaliyani Mahmudiyah (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2022)
Education is the process of changing the attitude and behavior of a person or group of people in an effort to mature humans through teaching and training. Current mathematics learning due to Covid 19 means that learning is not very efficient and cannot meet face to face between teachers, students and their friends. Therefore, because of the Covid 19 pandemic, students are asked to study at home using e-learning learning that utilizes social media. This study used a descriptive qualitative approach with research subjects as school principals, vice curricula, class teachers and fourth grade students. Data collection methods used are observation, interviews and documentation. The data analysis used is the Miles and Huberman model with data reduction techniques, data presentation and drawing conclusions. The results of the research regarding the implementation of e-learning mathematics for class IV MI-Azhar students are the implementation of learning that is carried out without face-to-face meetings between teachers and students as well as accessing the internet network and using social media to exchange information and interaction. Among them, namely by using the WhatsApp application, Google Meet and YouTube. Then the supporting factors for e-learning are the very rapid development of IT, a good and stable signal network. Meanwhile, the inhibiting factors for e-learning are unstable internet networks, unavailability of internet package quotas, substandard grades and a lack of understanding of math material. After that, the e-learning learning solution, namely the teacher provides relief such as additional time and excuses students who have problems in an unstable signal network and gives additional assignments to students who have grades below standard, and allows students to ask the teacher via private chat about incomprehensible material.